Structural geology: principles, concepts, and problems (3rd edition), by R.D.Hatcher, Jr. and C.M. Bailey, 2019 - Stawikowski, Wojciech (Geologos, 2022)
Structural geology: principles, concepts, and problems (3rd edition), by R.D.Hatcher, Jr. and C.M. Bailey, 2019. Oxford University Press/Academic US, 656 pages. Hardback: price 149.99, ISBN 9780190601928.